On precipitation of struvite (MgNH4PO4.6H2O) - Stefanus Muryanto (Journal of Science and Science Education, 2017)
Excessive input of N and P into water bodies causes eutrophication which leads to deterioration of aquatic evironments and has adverse effects naturally and economically. It is therefore urgent to remove N and P from wastewater prior to disposal into inland and coastal waters. Among the various removal methods, controlled struvite precipitation is preferred. Struvite (MgNH4PO4.6H2O) precipitates uncontrollably under the specific conditions producing a scale deposit causing persistent problems in industries and wastewater treatment plants. The scale deposit clogs the piping system and impair plant equipment. On the other hand, thanks to its composition and properties, struvite is a potential fertilizer. In medical field, struvite is a common component of kidney stones. A number of process parameters govern the struvite precipitation. This paper briefly presents these parameters: pH, molar ratios, temperature, mixing, and presence of foreign ions. pH level is considered as the most important variable affecting the precipitation of struvite and the pH level: 9.5 to 10.5 is seen as the optimum. For an effective precipitation the molar ratios of the struvite components, i.e. Mg:N:P should be at least unity. With regard to struvite solubility, the effect of temperature, in the range of 21oC to 49oC, is conflicting, which is probably due to different experimental conditions. Whilst agitation is not regarded as a decisive parameter, the influence of foreign ions, notably divalent metal ions, on struvite morphology and change of crystal phases is significant.